2010
DOI: 10.1021/jp106542v
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Atomistic View on the Electronic Relaxation in Light-Harvesting System II

Abstract: Aiming at a better understanding of the molecular details in light absorption during photosynthesis, spatial and temporal correlation functions as well as spectral densities have been determined. At the focus of the present study are the light-harvesting II complexes of the purple bacterium Rhodospirillum molischianum. The calculations are based on a time-dependent combination of molecular dynamics simulations and quantum chemistry methods. Using a 12 ps long trajectory, different quantum chemical methods have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
295
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(309 citation statements)
references
References 102 publications
(358 reference statements)
11
295
2
1
Order By: Relevance
“…We use MD simulations to generate R(t) and TDDFT excited-state calculations to obtain ǫ(R), which is consistent with the models proposed previously [35][36][37][38][39] Thus, in contrast to many studies based on a quantum master equation, this approach can describe the system-bath coupling in complete atomistic detail.…”
Section: Theorymentioning
confidence: 56%
See 1 more Smart Citation
“…We use MD simulations to generate R(t) and TDDFT excited-state calculations to obtain ǫ(R), which is consistent with the models proposed previously [35][36][37][38][39] Thus, in contrast to many studies based on a quantum master equation, this approach can describe the system-bath coupling in complete atomistic detail.…”
Section: Theorymentioning
confidence: 56%
“…A similar approach has been previously applied to small lightharvesting systems such as the FMO complex [37][38][39] and light-harvesting complexes II (LHII) of purple bacteria [35,36]. For a large number of BChls present in the chlorosome, it is computationally unfeasible to calculate site energies of all pigment molecules along an MD trajectory.…”
Section: Theorymentioning
confidence: 99%
“…Recent molecular dynamics (MD) simulation studies on the Fenna-Mathews-Olsen (FMO) excitation energy transfer network, 11,12 the light harvesting complex 2 (LHII) photosynthetic light harvesting complex 13 and the reaction center complex, 14 however, show no significant correlation in site energy fluctuations after averaging, and similar findings have been reported from calculations for the PE545 15 light harvesting system. However, Kleinekathöfer and co-workers, for example, have found that in FMO, 11 there is evidence of correlations in fluctuations of site energy and inter site electronic couplings and electronic coupling-electronic coupling correlations that are more significant compared to the apparently uncorrelated site energy fluctuations.…”
Section: Introductionmentioning
confidence: 58%
“…Several theoretical groups [11][12][13][14][15] have begun exploring detailed microscopic simulation models looking for different types of environment driven correlated fluctuations in chromophore electronic properties. The ubiquitous finding from the various photosynthetic energy transfer systems studied so far is that fluctuations in site energies seem to be such that on average they are uncorrelated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation